2016
DOI: 10.1111/bcp.13017
|View full text |Cite
|
Sign up to set email alerts
|

The medication reconciliation process and classification of discrepancies: a systematic review

Abstract: We suggest that clear and consistent information on prevalence, types, causes and contributory factors of medication discrepancy are required to develop suitable strategies to reduce the risk of adverse consequences on patient safety. Therefore, to obtain that information, we need a well-designed taxonomy to be able to accurately measure, report and classify medication discrepancies in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 109 publications
2
69
0
5
Order By: Relevance
“…Almanasreh et al . in their systematic review reported that a majority of studies related to medication reconciliation process used an empirical classification of discrepancies 26. In the same review, they suggested that “in order to understand the medication reconciliation process and identify the strategies for standardization, we need to clearly define and classify medication discrepancies as these are the only quantitative measures related to the medication reconciliation process”.…”
Section: Discussionmentioning
confidence: 99%
“…Almanasreh et al . in their systematic review reported that a majority of studies related to medication reconciliation process used an empirical classification of discrepancies 26. In the same review, they suggested that “in order to understand the medication reconciliation process and identify the strategies for standardization, we need to clearly define and classify medication discrepancies as these are the only quantitative measures related to the medication reconciliation process”.…”
Section: Discussionmentioning
confidence: 99%
“…Medication error may include the addition, withdrawal or changed dosage of a drug without documentation as stated by Midlöv et al [3], while medication discrepancy is a wider concept commonly also including changes in the mode or frequency of administration [4,5]. However, no clear and uniform definition exists [6].…”
Section: Introductionmentioning
confidence: 99%
“…We only would obtain a BPMH compared with a gold standard medication list after talking with patients and/or caregivers. Using the PharmaCloud system, we implemented medication reconciliation to find medication discrepancy as an unintended error in prescribing admission medications . The PharmaCloud system has been shown to improve the quality of care and prevent 5.83% of duplicated prescriptions .…”
Section: Discussionmentioning
confidence: 99%
“…Using the PharmaCloud system, we implemented medication reconciliation to find medication discrepancy as an unintended error in prescribing admission medications. 14…”
Section: Discussionmentioning
confidence: 99%